Paths to multimorbidity: a longitudinal perspective on disease accumulation in Catalonia, Spain. - Ahmed, Sahar M A; Permanyer, Iñaki; Solé-Auró, Aïda (European Journal of Public Health, 2026)
With increasing life expectancy, multimorbidity represents a growing global challenge, affecting quality of life. We analyzed electronic health records of individuals aged 45–74 from Catalonia, Spain (2007–2021), who were healthy at the end of 2007. We use sequence and cluster analysis to describe and categorize monthly disease accumulation patterns, from healthy to one or multiple conditions or death, involving four disease groups with the highest global morbidity and mortality burdens. We further investigate the association between identified clusters and sociodemographic factors and the association of cluster membership with healthcare utilization. Approximately 36% of individuals remained healthy throughout the study, while the remainder transitioned to single or multiple morbidity and/or died. A higher number of conditions in a given month increased transition probability, with metabolic and hypertensive conditions being the most common entry points. We identified nine disease accumulation trajectories linked to sociodemographic characteristics: Women were more likely to be in clusters involving neurodegenerative conditions and men in those involving cardiovascular and cancer conditions. Higher-income individuals were more likely to be in lower morbidity clusters, except the cancer multimorbidity cluster. Healthcare utilization was elevated in all clusters relative to the healthy group, with notably higher emergency use in cardiovascular clusters and more hospital admissions in cancer-related clusters. The study shows that disease accumulation follows identifiable patterns linked to sociodemographic factors and underscores the propagative nature of multimorbidity. Further, healthcare utilization is shaped more by condition type than by the number, highlighting the need for targeted health services.